Kensur Nawang Nima’s Treatise “The Lamp of Collected Quotations from Classical Works of the Buddhist History”: the Genesis of the Buddhist Monastic System in Northwest China - Andrey A. Bazarov; Vladimir V. Khartayev (Гуманитарный вектор, 2020)
The article is devoted to the analysis of the Buddhist monastic history in Northwest China, described in the treatise of the Buryat scholar Kensur Nawang Nima “The lamp of collected quotations from classical works of the Buddhist history”. This work is an example of Buddhist historical thought, which was developed in the traditional culture of the Buryats in the pre-revolutionary period. The authors of the article claim that “The lamp of collected quotations” has a specificity of presentation, determined by the author’s personality, historical and cultural circumstances. This specificity is related to the post-classical period of the history of Tibetan scholasticism, within which the work was written. Buddhist historical thought tried to understand the results of the most important stages of the Buddhist history in the vast region based on the works of previous generations. The treatise can be described as a scholastic work and Nawang Nima as an outstanding scholar and theorist of his time. Analysis of the structure of the work has showed that the author focused primarily on the history of the Geluk School, which he belonged to. Due to this specificity, most of the text is devoted to the biography of the founder of the school Je Tsongkhapa. The volume of work directly related to the history of Buddhist monasteries in northwestern China is extremely small. Nawang Nima describes the Genesis of the Geluk Buddhist monasteries: Chacung (bya khyung), Kumbum (sku ‘bum byams pa gling), Gonlung (dgon lung byams pa gling), Ganden (lga ldan dam chos gling), Rongwo (rong bo dgon chen), Labrang (bla brang bkra shis ‘khyil), Chone (сone dgon chen), etc. This fragment of the work “The lamp of collected quotations from classical works of the Buddhist history” is a fundamental historical description of the most important religious and cultural processes in the territories of Inner Asia in the period from the 19th up to the 20th century.